Penerapan Nilai Wajar Untuk Penilaian Aset Perusahaan Perbankan Pada Bank Permata, Tbk. - Median Wilestari; Wiwi Afriani (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
Indonesian Financial Accounting Standards (PSAK) confirm that asset assessment should be used fair value, therefore entities have to follow it from the previous application. Indonesian Financial Accounting Standard (PSAK) is a framework of accounting procedure to provide accounting financial statement which consist of standard of recording, preparation, treatment and providing financial statement. Valuation techniques used to measure fair value to maximize the use of observable relevant input and minimize the use of Unobservable relevant input. This study is using qualitative method which covert into quantitative by giving the weight value for the purpose of providing the preliminary understanding about implementation of fair value disclosure with valuation of asset from PT. Bank Permata Tbk. financial statement using primary data with collecting the data using interview and questionnaire. The overall result of fair value measurement of asset valuation from banking industry in PT. Bank Permata Tbk has been considered as appropriate, it is due to from the questionnaire 19 out of 20 questions were answered in accordance with the PSAK 68. Based on result of analysis, it is found that the question number 12 were not answered in accordance with PSAK 68 paragraph 74 with regards to the entities is prioritize the fair value hierarchy compare than the input, in other hand according to PSAK 68 paragraph 74 the priority should be the input than fair value hierarchy.